Analisis Kesalahan Penggunaan Kata Baku dalam Karangan Narasi Siswa Kelas VI Sekolah Dasar - Dewi, Atika; Darmuki, Agus; Fathurohman, Irfai (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the misuse of standard words in narrative essays written by sixth-grade elementary school students, focusing on morphological aspects, particularly affixation, reduplication, and compound word. The research employed a qualitative approach with a descriptive method. Data were collected from 23 narrative texts written by students at SDN Soneyan 02 through a writing assignment themed around the month of Ramadan. The findings revealed various morphological errors. Affixation errors included the omission of affixes and incorrect separation of affixes. Reduplication errors appeared in the use of numerical and symbolic instead of proper repeated forms. In addition, compound word errors were found in the form of incorrectly joined compound words. These findings indicate students' limited understanding of standard word formation rules, influenced by informal language use and low exposure to formal written texts. The study concludes that these errors stem from insufficient conceptual understanding of morphology, the influence of informal communication habits, and a lack of consistent corrective feedback from teachers. This research is limited to morphological errors and suggests that future studies explore syntactic, semantic, or pragmatic aspects for a more comprehensive understanding of students’ linguistic competence.